The Role of BMT in Improving Household Financial Management - Irfan Nurfalah; Muhammad Taufiq (Management and Sustainability, 2022)
Lack of capital is a major obstacle in doing business, especially when the business is classified as a micro small business. The capital factor is an obstacle to the development of a business. So if this micro small business owner wants to expand, he must borrow or credit to credit institutions such as : BPR, BPRS, Banks and other financial institutions. However, a new problem arises from BPR, namely that the minimum credit for businesses is Rp. 5 million plus interest. In response to this, Islamic economic experts created a concept of financing and savings up to a nominal value below Rp. 1 million even Rp. 100 thousand is still served. The financial institution is Baitul Maal wat Tamwiil (BMT). BMT is a solution for individuals who have home-based businesses to expand. This study will look at the role played by BMT and how maqasid sharia reviews this role.